The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2010
DOI: 10.1093/rpd/ncq479
|View full text |Cite
|
Sign up to set email alerts
|

Thermoluminescence solid-state nanodosimetry--the peak 5A/5 dosemeter

Abstract: The shape of composite peak 5 in the glow curve of LiF:Mg,Ti (TLD-100) following 90 Sr/ 90 Y beta irradiation, previously demonstrated to be dependent on the cooling rate used in the 4008 8 8 8 8C pre-irradiation anneal, is shown to be dependent on ionisation density in both naturally cooled and slow-cooled samples. Following heavy-charged particle high-ionisation density (HID) irradiation, the temperature of composite peak 5 decreases by ∼58 8 8 8 8C and the peak becomes broader. This behaviour is attributed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 26 publications
(36 reference statements)
0
6
0
Order By: Relevance
“…First, it can be compared with Monte Carlo simulations done for the purposes of nanodosimetry [26]. Second, it will be possible to compare this dependence (correspondingly modified) with dosimetric experiments [27,28]. At this point, it is possible to use the dependence shown in Fig.…”
Section: A Damage Complexity Distribution From the Random Walk Approachmentioning
confidence: 99%
See 2 more Smart Citations
“…First, it can be compared with Monte Carlo simulations done for the purposes of nanodosimetry [26]. Second, it will be possible to compare this dependence (correspondingly modified) with dosimetric experiments [27,28]. At this point, it is possible to use the dependence shown in Fig.…”
Section: A Damage Complexity Distribution From the Random Walk Approachmentioning
confidence: 99%
“…6 is shorter than 10 nm. Even though, this size is about 1000 times smaller (for glial cells) than that of the cell's nucleus [7]; it plays a significant role in calculations of the probability of cell death and will be critical for the comparisons with nano-dosimetric data [26][27][28]31].…”
Section: Dose Gymentioning
confidence: 99%
See 1 more Smart Citation
“…One of the approaches is to measure number of ionizations caused by radiation in gaseous targets of millimetric dimensions and recalculate the result to the biological nanometric sites using scaling procedure [1]. Another approach is to study thermoluminescent recombination between charge carriers trapped in centers of ~2 nm dimensions under influence of ionizing radiation [2].…”
Section: Introductionmentioning
confidence: 99%
“…Peak 5a, a low-temperature component of composite peak 5, is believed to arise from joint e -h capture in the TC/LC molecular complex and this 'two-energy-transfer' event is preferred at HID compared with the 'single-energy transfer' event giving rise to peak 5 (electron capture only) (3) . It has been suggested that the ratio 5a/5 can provide a nanodosimetric measurement of average ionisation density in the 'nanoscopic' volume comprising the TC/LC molecular complex giving rise to peaks 5a and 5 (4) ; (3) the decrease in the relative efficiency following HID/HCP irradiation, which has been modelled by track structure theory (TST) with some degree of success (5) . However, the TST premise that the radiation action of HCPs is exclusively due to the dose delivered by the secondary electrons liberated by the HCP slowing down has never been subjected to a stringent test.…”
Section: Introductionmentioning
confidence: 99%